HUBUNGAN ANTARA ADVERSE CHILDHOOD EXPERIENCE DAN SELF-CRITICISM PADA INDIVIDU DEWASA MUDA DENGAN ATTACHMENT STYLE SEBAGAI MODERASI - Valerie Purnomo; Zahrasari Lukita Dewi (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2023)
Self-evaluation evolves because of all the experiences they have; experiences can alter selfevaluation. Indonesian children may encounter developmental disruption in the form of Adverse Childhood Experiences (ACE), leading to increased self-criticism and negative self-assessment. On the other hand, there are various protective characteristics against adverse childhood experiences, one of which is attachment styles, which urge researchers to perform study on the association between ACE and self-criticism mediated by attachment styles in early adult individuals. The ACE Questionnaire, Levels of Self-Criticism, and Relationship Style Questionnaire were used to assess ACE, self-criticism, and attachment styles, which were then moderately analyzed using PROCESS. 223 participants' data (ranging from 19 to 40 years old) were gathered via digital forms. The results of the moderation calculation revealed that ACE was considerably positively connected to the level of self-criticism. Attachment styles—negative with Secure and positive with Preoccupied, Fearful, and Dismissing—have a major impact on one's level of self-criticism. Individuals who experience ACE and have an attachment style of Dismissingare more prone to experience strong Internalized Self-Criticism. Including ACE characteristics such as socioeconomic position, bullying, or peer rejection in the calculation might broaden the picture of ACE and highlight their distinct impact on self-criticism levels.